2019
DOI: 10.1164/rccm.201903-0511oc
|View full text |Cite
|
Sign up to set email alerts
|

Overlap of Genetic Risk between Interstitial Lung Abnormalities and Idiopathic Pulmonary Fibrosis

Abstract: A list of SPIROMICS investigators may be found before the beginning of the REFERENCES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 58 publications
4
68
0
Order By: Relevance
“…In addition, subjects with ILA show a higher frequency of the gain-of-function MUC5B common variant gene [5][6][7]. More recently, a genome-wide association study (GWAS) performed in individuals with ILA from six different cohorts, confirmed this association and described novel genome-wide associations near IPO11 (rs6886640), FCF1P3 (rs73199442), and near HTR1E (rs7744971) gene [8].…”
Section: Introductionmentioning
confidence: 87%
“…In addition, subjects with ILA show a higher frequency of the gain-of-function MUC5B common variant gene [5][6][7]. More recently, a genome-wide association study (GWAS) performed in individuals with ILA from six different cohorts, confirmed this association and described novel genome-wide associations near IPO11 (rs6886640), FCF1P3 (rs73199442), and near HTR1E (rs7744971) gene [8].…”
Section: Introductionmentioning
confidence: 87%
“…The MUC5B promoter variant has been associated with interstitial lung abnormalities (ILAs) in both families 132 and population-based cohorts. [133][134][135] Several peripheral blood biomarkers have been associated with early interstitial changes in families 131 or general populationbased cohorts [136][137][138][139] ; however, none of these biomarkers is currently approved or available for clinical use. The role of environmental exposures as a determinant of disease penetrance and phenotype has not been well studied; identifying modifiable risk factors could enable preventive strategies in high-risk individuals.…”
Section: Implications For Relatives Of Fip Patientsmentioning
confidence: 99%
“…In the last decade, a number of studies assessing radiological changes in longitudinal cohorts of people without obvious IPF-identified parenchymal changes, referred to as interstitial lung abnormalities (ILAs), have demonstrated an increase in both all-cause mortality and mortality from pulmonary fibrosis (3, 4), raising the prospect that ILAs may be the precursor lesions for IPF. Furthermore, there is overlap in the genetic architecture of IPF and ILA (5), and, indeed, serum biomarkers associated with pulmonary fibrosis are associated with ILA (6). This raises two fundamental questions: 1) are ILAs a precursor lesion for IPF and, if so, 2) should at-risk populations be screened for them?…”
Section: Yonis H Mortaza S Baboi L Mercatmentioning
confidence: 99%
“…Frank and colleagues showed that Wnt signaling is reactivated during alveologenesis and leads to proliferation of type 2 alveolar epithelial cells (AECs), whereas inhibition of Wnt signaling decreased proliferation and promoted transdifferentiation of type 2 AECs to type 1 AECs (3). Increased Wnt/b-catenin activity occurs in patients with BPD, whereas inhibition of WNT/b-catenin signaling attenuates hyperoxia-induced lung injury in neonatal rodent models (4)(5)(6).…”
Section: The Wnt Signaling Pathway and The Development Of Bronchopulmmentioning
confidence: 99%